Amyloid precursor protein protects neuronal network function after hypoxia via control of voltage-gaited calcium channels - Hefter, Dimitri; Kaiser, Martin Erich; Weyer, Sascha W.; Papageorgiou, Ismini E.; Both, Martin; Kann, Oliver; Müller, Ulrike C.; Draguhn, Andreas (The journal of neuroscience, 2016)
Acute cerebral ischemia and chronic neurovascular diseases share various common mechanisms with neurodegenerative diseases, such as disturbed cellular calcium and energy homeostasis and accumulation of toxic metabolites. A link between these conditions may be constituted by amyloid precursor protein (APP), which plays a pivotal role in the pathogenesis of Alzheimer′s disease, but has also been associated with the response to acute hypoxia and regulation of calcium homeostasis. We therefore studied hypoxia-induced loss of function and recovery upon reoxygenation in hippocampal slices of mice lacking APP (APP−/−) or selectively expressing its soluble extracellular domain (APPsα-KI). Transient hypoxia disrupted electrical activity at the network and cellular level. In mice lacking APP, these impairments were significantly more severe, showing increased rise of intracellular calcium, faster loss of function, and higher incidence of spreading depression. Likewise, functional recovery upon reoxygenation was much slower and less complete than in controls. Most of these deficits were rescued by selective expression of the soluble extracellular fragment APPsα, or by pharmacological block of L-type calcium channels. We conclude that APP supports neuronal resistance toward acute hypoxia. This effect is mediated by the secreted APPsα-domain and involves L-type calcium channels. - SIGNIFICANCE STATEMENT Amyloid precursor protein (APP) is involved in the pathophysiology of Alzheimer's disease, but its normal function in the brain remains elusive. Here, we describe a neuroprotective role of the protein in acute hypoxia. Functional recovery of mouse hippocampal networks after transient reduction of oxygen supply was strongly impaired in animals lacking APP. Most protective effects are mediated by the soluble extracellular fragment APPsα and involve L-type calcium channels. Thus, APP contributes to calcium homeostasis in situations of metabolic stress. This finding may shed light on the physiological function of APP and may be important for understanding mechanisms of neurodegenerative diseases.